2021
DOI: 10.1021/acsfoodscitech.0c00049
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Hemp (Cannabis sativa L.) and Dill Seed (Anethum graveolens) Improve Physicochemical Properties, Oxidative Stability, and Sensory Attributes of Broiler Meat

Abstract: This study was undertaken to unravel the potential of dietary hemp and dill seed for improving the physicochemical properties, oxidative stability, and sensory attributes of fresh (0 day) and stored broiler meat (15 and 30 days). A total of 192 straight-run day-old Cari-Vishal broiler chicks with an average weight of 42 g were grouped randomly into six groups and supplemented with varying dietary doses of hemp seed (HS) alone or combined with dill seed (DS) as a percentage of basal diet (BD), viz., diet T1 (BD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Several studies have indicated that incorporating alphalinolenic acid (ALA)-rich diets can strongly infuence the fatty acid composition in the egg yolk and hen's liver, particularly in regards to ALA, EPA, and DHA [16,32]. Research in the realm of incorporating hemp seed (HS) into the dietary regimen of laying hens predominantly centers on the utilization of whole hemp seeds, hemp oil, or other derivatives and products derived from the hemp plant [32][33][34][35]. Both birds and humans depend strongly on their liver for lipid metabolism [36].…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have indicated that incorporating alphalinolenic acid (ALA)-rich diets can strongly infuence the fatty acid composition in the egg yolk and hen's liver, particularly in regards to ALA, EPA, and DHA [16,32]. Research in the realm of incorporating hemp seed (HS) into the dietary regimen of laying hens predominantly centers on the utilization of whole hemp seeds, hemp oil, or other derivatives and products derived from the hemp plant [32][33][34][35]. Both birds and humans depend strongly on their liver for lipid metabolism [36].…”
Section: Resultsmentioning
confidence: 99%
“…The dill plant ( Anethum graveolens L.) from the Apiaceae family contains glycosides, saponins, tannins, terpenoids, steroids, flavonoids, phlobatanin, cardiac glycoside, anthraquinone, gallic acid, catechin, chlorogenic acid, luteolin and epicatechin. It has valuable health benefits [ 47 , 48 ], being able to reduce coliforms and increase lactobacilli in the caecum and jejunum [ 4 ]. Feeding 0.4 and 0.6% dill in the diet of broiler chicks has the potential to improve performance, reduce cholesterol and triglycerides, and improve microbial flora [ 49 ].…”
Section: Herbal Feed Additivesmentioning
confidence: 99%